PENGEMBANGAN MEDIA FLIPBOOK BERDASARKAN MODEL ADDIE DALAM PEMBELAJARAN KECEPATAN DAN DEBIT KELAS V SD - Farah Nabilah; Komariah Komariah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The lack of use of learning media in learning mathematics makes it difficult for students to understand learning materials, especially in speed and debit learning. There is a need for learning media that can make students more interested and more understanding when learning speed and debit. There is a solution, namely to develop digital learning media in the form of flipbooks. Based on this background there is a general problem formulation, namely how to develop flipbook media based on the ADDIE model in learning speed and debit for grade V elementary schools. With the aim of developing flipbook media based on the ADDIE model in learning speed and debit for fifth-grade elementary school. The flipbook learning media is based on the ADDIE model with research designs, namely development research and design and development research methods. The participants of this study were fifth-grade students and fifth grade teachers. From the results of the study, the responses of students and teachers were very positive towards this flipbook media. Based on the results of the assessment of the flipbook learning media product from the material, media, and language experts, it obtained a percentage of 86.22% with the "Very Valid" category. Then the results of student responses get a percentage of 90.55% with the "Very Valid" category, while the results of teacher interviews conclude that flipbook media is feasible to use. So based on these results, this flipbook media product is feasible to use during the learning process at school.